2008
DOI: 10.1038/npp.2008.219
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of Inferior Parietal Lobules in Prospective Memory Impairment during Acute MDMA (Ecstasy) Intoxication: An Event-Related fMRI Study

Abstract: Prospective memory refers to the realization of delayed intentions. Several studies have shown that 3,4-methylenedioxy-methamphetamine (MDMA) users perform worse on measures of prospective memory as compared to nondrug users. Interpretation of these data may be limited because of polydrug use, psychosocial stressors, and increased psychopathology that have been reported in MDMA users. This study was designed to directly assess the pharmacological effect of MDMA on prospective memory and brain activity in a dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 50 publications
9
40
1
Order By: Relevance
“…GLM analyses revealed that overall, MDMA decreased immediate recall in the WLT, increased the number of prospective memory failures in the prospective memory task and increased localization error in the spatial memory task. These results are fully in line with previous studies that have reported identical memory impairments during intoxication with MDMA Ramaekers, 2005, 2007;Ramaekers et al, 2009), as assessed in identical memory paradigms. These results basically indicate that the current memory paradigms were sensitive to the impairing effects of MDMA and should serve as reliable models to assess changes in MDMAinduced memory impairments after pretreatments with 5-HT 1A and 5-HT 2A receptor blockers, the main goal of this study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…GLM analyses revealed that overall, MDMA decreased immediate recall in the WLT, increased the number of prospective memory failures in the prospective memory task and increased localization error in the spatial memory task. These results are fully in line with previous studies that have reported identical memory impairments during intoxication with MDMA Ramaekers, 2005, 2007;Ramaekers et al, 2009), as assessed in identical memory paradigms. These results basically indicate that the current memory paradigms were sensitive to the impairing effects of MDMA and should serve as reliable models to assess changes in MDMAinduced memory impairments after pretreatments with 5-HT 1A and 5-HT 2A receptor blockers, the main goal of this study.…”
Section: Discussionsupporting
confidence: 82%
“…Conditions were separated by minimum washout period of 7 days to avoid cross-condition contamination. The 75 mg dose of MDMA was selected because it falls within the normal range of and has been consistently shown to impair memory performance and produce robust subjective mood changes in a number of previous studies from our lab Ramaekers, 2005, 2007;Kuypers et al, 2006;Ramaekers et al, 2009). Doses of pindolol 20 mg and ketanserin 50 mg represent regular therapeutic doses that block B40% of 5HT 1A receptors and 91% of 5HT 2 receptors, respectively (Brogden and Sorkin, 1990;Rabiner et al, 2000;Sharpley et al, 1994).…”
Section: Treatments and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective memory task (PMT) The PMT was developed to examine prospective memory performance (Ramaekers et al 2009b). The subjects were shown the letter A or B in the middle of a computer screen.…”
Section: Performance Testsmentioning
confidence: 99%
“…Furthermore, reduced activity in areas of the parietal cortex, following acute MDMA administration, was shown to be directly associated with impaired PM performance (Ramaekers et al 2009). …”
Section: Discussionmentioning
confidence: 99%